Drivers of value for money public private partnership projects in Malaysia - Ismail, Suhaiza (Emerald Group Publishing Limited, 2013)
Purpose – The purpose of this paper are twofold. First, it aims to investigate the factors that enhance the VFM achieved from PPP projects in Malaysia. Second, it aims to examine the differences in the perceptions of public and private sectors pertaining to the VFM factors of PPP implementation in Malaysia. Design/methodology/approach – A questionnaire survey was used to elicit the perceptions of the public and private sectors concerning the VFM drivers for PPP projects in Malaysia; 122 usable responses were obtained and analysed using SPSS to rank the importance of the factors and to examine the differences in the perceptions between the government and private sectors. Findings – The results reveal that two factors are perceived as “most important” to enhance the achievement of VFM for PPP implementation in Malaysia – “private sector technical innovation” and “competitive tender”. In terms of the differences in the perceptions of the public and private sectors concerning the level of importance of the VFM drivers, the results reveal that there are significant differences for half of the VFM factors. Originality/value – The exclusive contribution of this paper is that it highlights not only the factors that enhancing the VFM achievement for PPP projects in Malaysia, but also offers evidence concerning the differences in the perceptions of public and private sectors pertaining to the importance of the VFM factors.